Molecular interaction study of an anticancer drug, ponatinib with human serum albumin using spectroscopic and molecular docking methods - Tayyab, Saad; Sam, Si Enn; Kabir, Md Zahirul; Ridzwan, Nor Farrah Wahidah; Mohamad, Saharuddin (Elsevier, 2019)
Binding of a potent anticancer agent, ponatinib (PTB) to human serum albumin (HSA), main ligand transporter in blood plasma was analyzed with several spectral techniques such as fluorescence, absorption and circular dichroism along with molecular docking studies. Decrease in the K SV value with increasing temperature pointed towards PTB-induced quenching as the static quenching, thus affirming complexation between PTB and HSA. An intermediate binding affinity was found to stabilize the PTB-HSA complex, as suggested by the K a value. Thermodynamic analysis of the binding phenomenon revealed participation of hydrophobic and van der Waals interactions along with hydrogen bonds, which was also supported by molecular docking analysis. Changes in both secondary and tertiary structures as well as in the microenvironment around Trp and Tyr residues of HSA were anticipated upon PTB binding to the protein, as manifested from circular dichroism and three-dimensional fluorescence spectra, respectively. Binding of PTB to HSA led to protein's thermal stabilization. Competitive ligand displacement experiments using different site markers such as warfarin, indomethacin and ketoprofen disclosed the binding site of PTB as Sudlow's site I in HSA, which was further confirmed by molecular docking analysis. © 2019 Elsevier B.V.